2012
DOI: 10.1089/brain.2012.0105
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted brain networks in the aging HIV+ population

Abstract: Antiretroviral therapies have become widely available, and as a result, individuals infected with the human immunodeficiency virus (HIV) are living longer, and becoming integrated into the geriatric population. Around half of the HIV + population shows some degree of cognitive impairment, but it is unknown how their neural networks and brain connectivity compare to those of noninfected people. Here we combined magnetic resonance imaging-based cortical parcellations with high angular resolution diffusion tensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
(20 reference statements)
0
15
1
Order By: Relevance
“…Diffusion imaging may be used in conjunction with an automatically labeled set of regions from anatomical MRI to perform connectivity mapping and network analysis of the brain's fiber connections. Many analyses of brain connectivity have been conducted in this way (Dennis et al, 2012a, b;Dennis and Thompson, 2012;Jahanshad et al, 2011Jahanshad et al, , 2012Zalesky, 2009;Zhan et al, 2012). Connectivity matrices were compiled using a processing pipeline described previously (Braskie et al, 2012a, b;Dennis et al, 2012b;Jahanshad et al, 2011Jahanshad et al, , 2012Nir et al, 2012a, b).…”
Section: Subjects and Diffusion Imaging Of The Brainmentioning
confidence: 99%
“…Diffusion imaging may be used in conjunction with an automatically labeled set of regions from anatomical MRI to perform connectivity mapping and network analysis of the brain's fiber connections. Many analyses of brain connectivity have been conducted in this way (Dennis et al, 2012a, b;Dennis and Thompson, 2012;Jahanshad et al, 2011Jahanshad et al, , 2012Zalesky, 2009;Zhan et al, 2012). Connectivity matrices were compiled using a processing pipeline described previously (Braskie et al, 2012a, b;Dennis et al, 2012b;Jahanshad et al, 2011Jahanshad et al, , 2012Nir et al, 2012a, b).…”
Section: Subjects and Diffusion Imaging Of The Brainmentioning
confidence: 99%
“…22 This finding is also consistent with the more widespread deficits in brain structural connectivity (on diffusion tensor imaging scans) in HIV1 APOE e4 subjects. 31 These discrepancies in the effects of APOE e4 on HAND may also be partly attributable to racial differences among cohorts. A large longitudinal study found that only white but not black individuals with APOE e41 showed faster decline in semantic and working memory.…”
Section: Mri and Mrsmentioning
confidence: 99%
“…Fractional anisotropy (FA) is an index of the extent to which this motion is directionally constrained and, as validated in animal (Li et al, 2011) and post-mortem research (Schmierer et al, 2007), it reflects a combination of myelin thickness, fiber coherence and axon integrity. Studies using a priori selected candidate genes and SNPs have associated FA with genetic variation in NRG1 (McIntosh et al, 2008; Sprooten et al, 2009; Winterer et al, 2008), ErbB4 (Konrad et al, 2009; Zuliani et al, 2011), DISC1 (Sprooten et al, 2011b), NTRK1 (Braskie et al, 2012), BDNF (Chiang et al, 2011a) and APOE (Jahanshad et al, 2012), amongst others. However, FA is a complex, polygenic phenotype and for most complex phenotypes data-driven GWA have not implicated a priori candidate variants in their top results (Flint and Munafo, 2013; Stein et al, 2012), hence many more novel SNP-associations contributing to variation in FA could be discovered using GWA.…”
Section: Introductionmentioning
confidence: 99%